DIVERSIDADE BACTERIANA EM CARCINOMA PENIANO: UMA ABORDAGEM MICROBIÔMICA - DEUS, Amanda Jordão Silva de (2022)
Penile Carcinoma is rare and represents less than 0.5% of all cancers in men worldwide. In Brazil, it has incidence rates that vary between 2.9 and 6.8%, mainly affecting individuals with low socioeconomic and educational levels, especially in the North and Northeast regions. Poor hygiene in the genital region, made difficult by the absence of circumcision of the glans, leads to microbial proliferation and results in the accumulation of secretions, such as smegma, which can cause chronic inflammation of the epithelium and contribute to the establishment of the tumor. The advancement of molecular techniques applied to the identification of microorganisms has boosted knowledge about the relationship between the microbiological flora in some cancers. However, there are no reports on the microbiome in penile tumors. Thus, this work is a pioneer in identifying, through a microbiomic approach, the bacterial diversity in Penile Squamous Cell Carcinoma (PSCC), and its relationship with the etiopathogenesis of this tumor. For this, samples of tumor tissue paired with non-tumor tissues adjacent to the primary tumor were collected from 19 treatment-naïve patients with clinical and histopathological diagnosis of PSCC. All patients (age 62.6 ± 16.5 years) had HPV infection, most of them at high ongogenic risk (79%) with low educational level, 78.9% had tumors located in the glans and foreskin and 73% of the tumors were advanced. (pT2 or pT3), resulting in total (21%) or partial (73%) penectomy surgeries. Next-generation sequencing (SNG) was performed using DNA extracted from tumor and non-tumor tissues, and the genomic library was prepared following the protocol of Neoprospecta Microbiome Technologies, Brazil. The V3-V4 region of the 16S rRNA gene and the amplicons from each sample were indexed and sequenced using the MiSeq Sequencing System (Illumina Inc., USA). The quality of the sequences was evaluated by FastQC v.0.11.8 software. Bioinformatics analysis (DADA2, QIIME2 v.2020.2) was used to classify and assess microbiome diversity in both the primary tumor and adjacent non-tumor tissue. A bibliographic survey was carried out seeking microbiome data from non-tumor penile tissue and from HPV associated tumor tissues, with histopathology similar to PSCC. PICRUST2 was used to predict functional composition. In the global analysis of the samples, it was verified that the phyla Proteobacteria and Firmicutes, as well as the genera Alcaligenes and Fusobacterium, were the most abundant in both tissues, with the phyla Fusobacteroidota and Campylobacterota and the genera Fusobacterium and Chromobacterium being statistically significant when compared with their paired samples. We emphasize the occurrence of bacteria associated with the inflammatory process, both in phyla and in the most abundant genera, such as: Fusobacterium nucleatum and Prevotella. On the other hand, significant relative abundance of Mycobacterium was not observed. Although no statistical difference was observed in the alpha and beta diversities of the paired samples, stratified analysis of the patients showed that for advanced tumors (pT2 and pT3) there was a tendency for the formation of two distinct groups characterized by different bacterial genera (p=0,08). We identified that Prevotella is common for PSCC, SCCHN, CSCC and VC, while the genera Alcaligenes, Eubacterium, yurii group and Pseudoglutamicibacter are specific for PSCC. The functional analysis revealed 35 top pathways, among which six had the highest predictive power (p-value and difference in abundance): chitin degradation, myo-inositol degradation, myo-chiro and scyllo-inositol degradation, hexuronate degradation, sucrose biosynthesis and nylon-6 oligomer degradation. In addition, unique and abundant ASVs (Amplicon Sequence Variants) from the genera Alcaligenes, Streptobacillus and Bacillus were reported in tumor tissues (p<0.05) while unique ASVs from the genera Cupriavidus, Staphylococcus and Finegoldia were more abundant in adjacent non-tumor tissues (p<0.05). The results showed an abundant PSCC microbiota, but also with unique ASVs, in addition to presenting bacterial taxa and molecular pathways related to inflammatory processes, confirming the role of inflammation in the etiopathogenesis of PSCC, opening perspectives for public policies for prevention, prognosis and treatment.